Novas medidas de localiza????o a partir da an??lise de dist??ncia de pontos: um estudo emp??rico para a ind??stria da transforma????o na regi??o metropolitana de S??o Paulo - Lopes, J??lio C??sar da Cunha (2016)
Although there is a wide variety of measures to measure the levels of agglomeration and location of firms, the areal unit problem modifiable - MAUP - is always remembered in literature as a problem in regional science. The purpose of the research is to apply the newly developed tracing measures that surpass largely the MAUP problem. With unprecedented use in Brazil, these measures assess the level of sectoral location of manufacturing industry in the Greater S??o Paulo and the results show that the fabrication industries of automotive vehicles, trailers and bodies and clothing and accessories are more localized . On the other hand, the non-metallic minerals and pulp and paper segments have a higher dispersion in relation to the other.